(3GdRGhFO Ydi OjhGf GdCHjhQOi (B((3GdYQGbjGJ(B)s - (3CHh GdeXaQ eMeO Hf CMeO Hf eMeO GdbQTi GdCehj GdCHjhQOis; (3GdCHjhQOj , eMeO Hf CMeO Hf eMeO GdbQTj, CHh GdeXaQ,J (B507 (3g` s
(3ChdgG (B:s
(3bGd jeOM GdSdWGf GdeYXe eMeO Hf edc HfKGg hcfjJg CHh TLGY hgPg GdbUjOI NGQLI Yf GdYQGbjGJ EPJgjC fXegG HYO eG LeY GdOjhGf s
(3BNQgG (B:s
(3adPdc CeScJ Yf GdJQLjM hde CTJZd ajg HGdJQJjH hGdJTLjY hGbJUQJ Ydi gPG GdbOQ ef GdJdhjM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B314s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B75 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B774s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG (B- (3QGeHhQ (B((4)3949) s
Keywords: (3GdCOHs